Análise de implementação do PRONATEC/Bolsa Formação no Instituto Federal do Triângulo Mineiro (IFTM) 2012-2015 - Ruggiero, Maria Fernanda (Universidade Federal de São Carlos, 2016)
This research deals with a process analysis of implementation of the Nacional Program of Access to technical education and job/scholarship education in the Federal Institute of Education, Science and technology of the Triângulo Mineiro Campus Uberlândia and Uberlândia Centro. Between the years of 2012 and 2015, aiming to identify what form and factors of political-institutional conditioned the implementation and its sub processes and propose an instrument in order to evaluate the program. Primarily we aimed to identify the objectives of the program and the strategy of implementation developed by the Federal Govern, so the expected results could be achieved. From the recognition of the implementation strategy was built an evaluation model of the implementation of PRONATEC / Scholarship education in Federal Education Institutions. Afterwards through a case study, we sought to evaluate in what way some political-institutional variants condition the implementation of PRONATEC/SE. The data of the case study to recognize de conditioning factors of the implementation processes were collected by the management report, execution programme documents and a semi structured interview with the implementing agents of the program in a local level. The research results aim that the PRONATEC/SE in IFTM implementation was favored mainly by the commitment and active performance of the implementing agents in coordinating alongside with the demanding collaborators the course offers; by the infrastructure use and the local human resources in the institution and the payment of the student assistance to the students. The main obstacles found in the implementation process were the transference financial resource delay; reduced time to articulate the course offers; absence of clear goals to be achieved in a heterogeneous profile of the students
Keywords: PRONATEC/BF; Implementação; Avaliação; Implementation; Evaluation; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS